A method to improve quantum state fidelity in circuits executed on ibm’s quantum computers - Sisodia, Mitali; Shukla, Abhishek; de Almeida, Alexandre A.A. [UNESP]; Dueck, Gerhard W.; Pathak, Anirban (Canadian Science Publishing, 2021)
Recently, various quantum computing and communication tasks have been implemented using IBM’s superconductivity-based quantum computers. Here, we show that the circuits used in most of those works were not optimized and obtain the corresponding optimized circuits. Optimized circuits implementable in IBM quantum computers are also obtained for a set of reversible benchmark circuits. With a clear example, it is shown that the reduction in circuit cost enhances the fidelity of the output state (with respect to the theoretically expected state in the absence of noise) as fewer gates and less circuit depth introduce fewer errors during evolution of the state. Further, considering Mermin inequality as an example, it is shown that the violation of the classical limit is enhanced when we use optimized circuits. Thus, the present approach can be used to identify a relatively weaker signature of quantumness and to establish quantum supremacy in a stronger manner.
Keywords: IBM quantum processor; Mermin inequality; Optimization algorithm; Quantum circuit optimization; Reversible circuit optimization